South African Literature after the Truth Commission - Graham, S. author. aut Link
XI, 235 p.
Keywords: This book studies a broad and ambitious selection of contemporary South African literature, fiction, drama, poetry, and memoir to make sense of the ways in which these works 'remap' the intersections of memory, space/place, and the body, as they explore the legacy of apartheid.